EXPECTATIONS AND EXPERIENCES WITH PRESCRIBING CLINICIANS AMONG SHORT-STAY PATIENTS IN SKILLED NURSING FACILITIES. (16th November 2018) - Ryskina, K; Foley, K; Karlawish, J; Uy, J; Lott, B; Goldberg, E; Hodgson, N
Abstract: One in four Medicare beneficiaries discharged from hospitals to skilled nursing facilities (SNFs) for post-acute care (short-stay) are re-hospitalized or die within 30 days. While prescribing clinicians (physicians, nurse practitioners, and physician assistants) are considered integral to improving care coordination and transitions in care, little is known about the role of SNF prescribing clinicians in the experience of patients who transition from hospitals to post-acute care in SNFs. To better understand the experiences and expectations of patients receiving post-acute care in SNFs with their prescribing clinicians, we conducted a qualitative study using semi-structured patient interviews at five diverse (i.e., size, setting, and prescribing clinician staffing) SNFs between January and August 2018. Forty-eight patients (and their caregivers) transferred to the SNFs for short-term care 5–10 days prior to the interview were eligible to participate. Thematic analysis of the transcripts was performed to detect recurrent themes and divergent ideas with a focus on modifiable clinician-level factors that might improve patient experience. Analysis was stratified by patient cognitive impairment (measured by MOCA) and race. Member checks were conducted as a validation technique. The major theme that emerged was misleading expectations about the prescribing clinician (e.g., patients expected to continue seeing their hospital doctors). A majority of subjects (85%) reported transient interactions with their SNF prescribing clinician. Most (95%) had limited knowledge of the prescribing clinician(s) in SNFs and 60% reported feeling disempowered to discuss their care with the clinician(s). Patients with lower MOCA scores and minorities were more likely to report feeling disempowered.